Labour and social protection gaps impacting the health and well-being of workers in non-standard employment: An international comparative study - Signild Kvart; Isabel Cuervo; Virginia Gunn; Wayne Lewchuk; Kim Bosmans; Letitia Davis; Astrid Escrig-Piñol; Per-Olof Östergren; Eva Padrosa; Alejandra Vives; Alessandro Zaupa; Emily Q. Ahonen; et al. (PLoS ONE, 2025)
Background World economies increasingly rely on non-standard employment arrangements, which has been linked to ill health. While work and employment conditions are recognized structural determinants of health and health equity, policies aiming to protect workers from negative implications predominantly focus on standard employment arrangements and the needs of workers in non-standard employment may be neglected. The aim of this study is to explore workers’ experiences of gaps in labour regulations and social protections and its influence on their health and well-being across 6 countries with differing policy approaches: Belgium, Canada, Chile, Spain, Sweden, and the United States. Methods 250 semi-structured interviews with workers in non-standard employment were analyzed thematically using a multiple case-study approach. Results There are notable differences in workers’ rights to protection across the countries. However, participants across all countries experienced similar challenges including employment instability, income inadequacy and limited rights and protection, due to policy-related gaps and access-barriers. In response, they resorted to individual resources and strategies, struggled to envision supportive policies, and expressed low expectations of changes by employers and policymakers. Conclusions Policy gaps threaten workers’ health and well-being across all study countries, irrespective of the levels of labour market regulations and social protections. Workers in non-standard employment disproportionately endure economic risks, which may increase social and health inequality. The study highlights the need to improve social protection for this vulnerable population.